Răspuns :
a ) 3x + 1 = x + 5
3x - x = 5 - 1
2x = 4
x = 4 : 2
x = 2
-----------------------------
b ) 2x = x + 3
2x - x = 3
x = 3
-----------------------------
c ) 24 : x = 6
x = 24 : 6
x = 4
-----------------------------
d ) x + 5 = 31
x = 31 - 5
x = 26
------------------------------
e ) 2x - 3 = 17
2x = 17 + 3
2x = 20
x = 20 : 2
x = 10
------------------------------
f ) 3( x + 1 ) - 2 = 16
3x + 3 - 2 = 16
3x + 1 = 16
3x = 16 - 1
3x = 15
x = 15 : 3
x = 5
3x - x = 5 - 1
2x = 4
x = 4 : 2
x = 2
-----------------------------
b ) 2x = x + 3
2x - x = 3
x = 3
-----------------------------
c ) 24 : x = 6
x = 24 : 6
x = 4
-----------------------------
d ) x + 5 = 31
x = 31 - 5
x = 26
------------------------------
e ) 2x - 3 = 17
2x = 17 + 3
2x = 20
x = 20 : 2
x = 10
------------------------------
f ) 3( x + 1 ) - 2 = 16
3x + 3 - 2 = 16
3x + 1 = 16
3x = 16 - 1
3x = 15
x = 15 : 3
x = 5
a)
3 x + 1 = x + 5
3 x - x = 5 - 1
2 x = 4
x = 4 : 2
x = 2
Verific: 3 × 2 + 1 = 2 + 5 = 7
b)
2 x = x + 3
2 x - x = 3
x = 3
2 × 3 = 3 + 3 = 6
c)
24 : x = 6
x = 24 : 6
x = 4
V: 24 : 4 = 6
d)
x + 5 = 31
x = 31 - 5
x = 26
V: 26 + 5 = 31
e)
2 x - 3 = 17
2 x = 17 + 3
2 x = 20
x = 20 : 2
x = 10
V: 2 × 10 - 3 = 20 - 3 = 17
f)
3 ( x + 1 ) - 2 = 16
3 x + 3 - 2 = 16
3 x = 16 - 1
x = 15 : 3
x = 5
Verific: 3 × ( 5 + 1 ) - 2 = 3 × 6 - 2 = 18 - 2 = 16
3 x + 1 = x + 5
3 x - x = 5 - 1
2 x = 4
x = 4 : 2
x = 2
Verific: 3 × 2 + 1 = 2 + 5 = 7
b)
2 x = x + 3
2 x - x = 3
x = 3
2 × 3 = 3 + 3 = 6
c)
24 : x = 6
x = 24 : 6
x = 4
V: 24 : 4 = 6
d)
x + 5 = 31
x = 31 - 5
x = 26
V: 26 + 5 = 31
e)
2 x - 3 = 17
2 x = 17 + 3
2 x = 20
x = 20 : 2
x = 10
V: 2 × 10 - 3 = 20 - 3 = 17
f)
3 ( x + 1 ) - 2 = 16
3 x + 3 - 2 = 16
3 x = 16 - 1
x = 15 : 3
x = 5
Verific: 3 × ( 5 + 1 ) - 2 = 3 × 6 - 2 = 18 - 2 = 16